CANONIC RELATIONS OF ANTHROPOMETRIC AND MOTOR SPACE BETWEEN STUDENTS AS FOOTBALL PLAYERS AND NON FOOTBALL PLAYERS - Fitim Arifi; Iber Alaj; Zenel Metaj; Sami Sermaxhaj; Jeton Nebiu (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
Taking into account morphological and motor status of students as football players and non-football players of the same age is meant by certain basic system of anthropometric latent dimensions which are developed with the influence of endogenous and exogenous factors and the impact of physical education classes and various trainings outside education process. While in motor space the research is defined in basic motorics and in situational motorics of the game of football, where in some of them important factor is genetic factor or born. Through this study we can conclude that the work that students do in schools during the physical education classes, will change with the students as football players who had the opportunity that except physical education classes to work as well during the week 3 to 4 trainings in the football school. For this research was taken the sample of 142 entities of 13 - years of age from them 71 students and active football players and 71 students that aren't active football players. The main purpose of this paper is verification of canonic relations, anthropometric space, and basic motor tests and situational motorics to the students as football players and non-football players and also we will verify the implementation and impact of anthropometric space parameters in basic motor tests and situational motorics.